Mitigating Carbon Emissions in Maritime Operations: A Case Study of Bakungan Port - Agus, Wikarno; Yusriani, Sri; Pambelum, Joni; Sholihah, Fajriyah Melati; Rozet, Stefly J. A. (RSF Conference Series: Business, Management and Social Sciences, 2023)
Baramulti Suksessarana, Tbk. (PT. BSSR), a mining company in Batuah Village, Kutai Kartanegara, operates a port facility in Bakungan Village powered entirely by electricity supplied by PLN. This energy source drives the crusher unit, OLC, and BLC (identified as significant energy users in the port area) and supports additional activities, such as office operations and control rooms. PT BSSR, having joined the B20 movement that emphasizes "Energy, Sustainability & Climate," supports PT PLN’s program targeting a reduction of 900 million tons of carbon emissions per year. Our research, therefore, centers on energy conservation and carbon emission reduction. PT BSSR inventoried all electrical energy-consuming units, compiled an electricity usage history, and created a baseline for consumption. A linear regression equation correlating energy consumption (kWh) with crushing product (MT) was derived from this baseline, establishing a benchmark for future conservation. We aimed to reduce the CO2e/MT Ratio or Greenhouse Gas Emissions in the Bakungan Port area from 0.44086 kg CO2e/MT to 0.3837 Kg CO2e/MT. Initiatives included implementing sensor monitoring and CCTV to prevent large rock entry, minimizing electrical "Start-Stops," conducting regular inspections and maintenance, and executing other conservation programs. The research led to a successful reduction in Greenhouse Gas/Carbon Emissions by 0.025e/MT, equivalent to 101.11 Tons of CO2e per year. This equates to a reduction of 0.169 kWh/MT or 680.689 kWh annually, yielding a cost saving of Rp 220.06/MT or a total of Rp 883,988,533 per year.